2017
DOI: 10.1158/0008-5472.can-16-0687
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 Prevents Calcium-Induced Progression of Early-Stage Prostate Tumors by Counteracting TRPC6 and Calcium Sensing Receptor Upregulation

Abstract: Active surveillance has emerged as an alternative to immediate treatment for men with low-risk prostate cancer. Accordingly, identification of environmental factors that facilitate progression to more aggressive stages is critical for disease prevention. Although calcium-enriched diets have been speculated to increase prostate cancer risk, their impact on early-stage tumors remains unexplored. In this study, we addressed this issue with a large interventional animal study. Mouse models of fully penetrant and s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 50 publications
1
36
0
Order By: Relevance
“…Thus, targeting TRPC6 channel function may be a viable approach to treat gastric cancer. Over the past decades, very few small molecular TRPC6 antagonists [15,16,25,2732] (examples shown in Chart 1) have been reported, and some of them have shown strong growth-inhibitory effects on cancer both in vitro and in vivo . Among them, vitamin D3 effectively reduced calcium-induced early-stage prostate tumorigenesis by down-regulating TRPC6 and the calcium sensing receptor both in vitro and in vivo [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, targeting TRPC6 channel function may be a viable approach to treat gastric cancer. Over the past decades, very few small molecular TRPC6 antagonists [15,16,25,2732] (examples shown in Chart 1) have been reported, and some of them have shown strong growth-inhibitory effects on cancer both in vitro and in vivo . Among them, vitamin D3 effectively reduced calcium-induced early-stage prostate tumorigenesis by down-regulating TRPC6 and the calcium sensing receptor both in vitro and in vivo [25].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, very few small molecular TRPC6 antagonists [15,16,25,2732] (examples shown in Chart 1) have been reported, and some of them have shown strong growth-inhibitory effects on cancer both in vitro and in vivo . Among them, vitamin D3 effectively reduced calcium-induced early-stage prostate tumorigenesis by down-regulating TRPC6 and the calcium sensing receptor both in vitro and in vivo [25]. The use of SKF96365, albeit being nonspecific, supported the results from siRNA silencing on the essential roles of TRPC6 channels in G2/M phase progression of gastric cancer cells and tumor formation in the xenograft model [27].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic inflammation promotes metastases and progression to castration-resistant prostate cancer [11,12]. CRP could predict tumor aggressiveness and potential treatment efficacy in patients with prostate cancer [13].…”
Section: Discussionmentioning
confidence: 99%
“…Data strongly suggested that the antitumor effect of vitamin D and calcitriol included a transcriptional down-regulation of TRPC6 calcium channels. Moreover, the proliferation of PC-3 prostate cancer cells was decreased by silencing the expression of TRPC6 (Bernichtein et al, 2017). Khatun et al, (2016) showed that calcitriol (1 uM, 72 h) and calcipotriol (1 uM, 72 h), a VDR agonist, inhibited the expression of KCa1.1 channels in MDA-MB-453 breast cancer cells.…”
Section: Steroid Hormone Regulation Of Ion Channels As a Potential Opmentioning
confidence: 99%